Derajat Kepadatan Lapis Pondasi Agregat Tanpa Penutup Aspal Menggunakan Metode Sand Cone pada Proyek Rekonstruksi Jalan Kecamatan Serai Serumpun, Kabupaten Tebo di Ruas Jalan Tanjung Aur Seberang-Malako Tinggi - Yumardi, Yumardi; Wijaya, Sucitra; Kutni, Darul; Rianto, Doli Jumat; Marwadi, Aji (Universitas Batanghari Jambi, 2024)
Road infrastructure is very important for the economic progress of Tanjung Aur Seberang village residents. Economic development in Tanjung Aur Village, Tebo Regency has significantly increased traffic levels. If this is not balanced by improving the quality of transportation facilities and infrastructure, then this could cause serious problems. Determining the value of the degree of density of the foundation layer aggregate (soil) class S in obtaining soil stability with safe conditions in accordance with the requirements of density standards is the aim of this research. The methods used are direct tests in the field and in the laboratory. Testing soil density in the field using a sand cone tool follows the provision stated in SNI 03-2828-1992, while testing soil density in the laboratory follows the provisions stated in SNI 1742-2008. Soil density testing intervals vary between 50 meters, 75 meters, 100 meters, 150 meters, 200 meters depending on location conditions. The results sand cone testing was carried out on roads from STA 2+000 to 3+800. In the first test with 9 test points, the field density was obtained below 95%, namely STA 2+100 (94,141%), STA 2 +550 (94,389%) and STA 3 +800 (94,289). Theses results indicate that the required standard degree of field density has not been achieved, so that the base layer of class S aggregate can be added and compaction can be carried out again. And from STA 0 + 005 to 4 + 200 in the second test with 26 test points. Test results using a sand cone tool show that the average water content value is 7.513% with a density reaching 98.846%. and these results were in accordance with applicable standard requirements.